PEMBERDAYAAN UKM MELALUI PENYULUHAN PENYUSUNAN LAPORAN KEUANGAN - Aprih Santoso; Ardiani Ika Sulistyawati; Nir Setyo Wahdi (Universitas Trisakti, 2021)
The main problem of UKM players in Pedurungan Tengah Village is that there is no financial report correctly and they still like the UKM players. The purpose of community service is to provide knowledge and understanding to UKM of Pedurungn Tengah Village in making financial reports correctly. This PKM uses extension methods. The result of PKM is that UKM players in Pedurungan Tengah Village can understand and increase their knowledge about the preparation of financial reports in carrying out their business activities. They can independently compile business financial reports so there is no need for assistance from the PKM FE Team of the University of Semarang.